The Role of Innovation in International Business on the Example of the Midea Group - Shaomin Li; Tatiana Ushkats (Communications of International Proceedings, 2021)
A changing world and global trends represent both challenges to be met and opportunities to be seized by creating and implementing innovation. The term "innovation" is now applied to almost all areas of economic and social processes, but this article will consider the impact of new ideas on the economy and business. The purpose of this article is to investigate the role and importance of innovation for international business, to trace the development of China's innovation policy and, by assessing the effectiveness of companies in the field of innovation, to determine the success factors in the development of innovation. In this paper, authors used such modern methods of scientific knowledge as an analysis, synthesis, induction, abstraction. The article identifies the success factors in the development of innovations in modern business on the example of the Chinese company Midea Group, which is known for the production of household appliances and commercial air conditioners. As a result of the study, the authors can conclude that a key factor in the success of most Chinese companies producing electronic equipment is their high innovative potential. In the case of Midea Group, it is safe to say that it is also of great importance to have the right organizational structure and clear strategic planning.
Keywords: Innovation; business; business innovation; Chinese innovation